Tuberculosis incidence trends in Saudi Arabia over 20 years: 1991-2010 - Ibrahim Al-Orainey (Annals of Thoracic Medicine, 2013)
Objective: To evaluate tuberculosis (TB) incidence rates and trends over a period of 20 years (1991-2010) and assess the impact of the National TB Control Program (NTP) on incidence trends. Methods: This is a retrospective study of TB surveillance data reported by the Ministry of Health. We evaluated TB incidence data by nationality, age, and region of the country and assessed incidence trends over 20 years of study. Chi-squared test was used to assess trend change and its significance. Results: There were a total of 64,345 reported TB cases over the study period. Of these 48% were Non-Saudis. TB annual incidence rate ranged between 14 and 17/100,000. For Saudis, the rate ranged between 8.6 and 12.2/100,000. Non-Saudis had 2-3 times higher incidence. Disease trend was rising over the first 10 years of the study period then it started to fall slightly. The incidence increased with age, but only people older than 45 years showed a declining trend. Regional variations were observed. Makkah and Jazan regions had the highest incidence rates. Disease trends were rising over the last 10 years in Makkah and Central regions. Conclusion: TB control seems to be facing some challenges in several regions of the Kingdom. NTP needs to evaluate and improve TB control strategies in order to reduce disease incidence to elimination levels.